2019
DOI: 10.1002/sop2.4
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Social Programs to Promote Economic Stability During Childhood

Abstract: Economic instability has increased in recent decades and is higher for families with low incomes and Black families. Such instability is thought to be driven primarily by precarious work and unstable family structure. In addition, the social safety net has become less of a stabilizing force for low‐income families, in part because benefits are often tied to employment and earnings. Too much change in economic circumstances may disrupt investments in children, parenting practices, and family routines—particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 199 publications
1
24
0
Order By: Relevance
“…For example, the games selected included activities for logic, problem-solving, visual search and attention, cognitive inhibition, set-shifting, verbal and nonverbal memory, color and shape recognition, and others. Previous studies have reported that the use of computer games as well as educational computer programs can benefit from academically relevant content and other cognitive skills [ 35 ]. Parents from the CG also reported that, following the supervised therapy program, their children had improved fine motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the games selected included activities for logic, problem-solving, visual search and attention, cognitive inhibition, set-shifting, verbal and nonverbal memory, color and shape recognition, and others. Previous studies have reported that the use of computer games as well as educational computer programs can benefit from academically relevant content and other cognitive skills [ 35 ]. Parents from the CG also reported that, following the supervised therapy program, their children had improved fine motor skills.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of Chinese visitors and the government has changed this situation altogether. The improved revenue generation has made remarkable progressive outcomes to support Pakistan’s economy ( Hardy et al, 2019 ). China has advertised Pakistani tourist destinations and made them more attractive for foreigners to visit them without any security-related concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We largely set aside the workings and child‐level benefits of income‐support policies. A recent Social Policy Report examined this field in detail (Hardy, Hill, & Romich, 2019). Evidence is accumulating on efforts to provide a universal basic income to all families as well (Hoynes & Rothstein, 2019).…”
Section: Overview—policy Action For Robust Childhoodsmentioning
confidence: 99%